2010
DOI: 10.2174/187152710791292567
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Oxidative Glutamate Toxicity: The Glutamate/Cystine Antiporter System xc¯ as a Neuroprotective Drug Target

Abstract: The glutamate/cystine antiporter system x(c)- transports cystine into cells in exchange for the important neurotransmitter glutamate at a ratio of 1:1. It is composed of a specific light chain, xCT, and a heavy chain, 4F2, linked by a disulfide bridge. Both subunits are localized prominently in the mouse and human brain especially in border areas between the brain and periphery including vascular endothelial cells, ependymal cells, choroid plexus, and leptomeninges. Glutamate exported by system x(c)- is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 0 publications
2
101
0
Order By: Relevance
“…This is further supported by the fact that in the present model system using immortalized HT-22 neurons cell membrane NMDA receptors are not expressed (41,42), and SK2 channel activation is neuroprotective even in the absence of extracellular Ca 2ϩ . Recent findings on the role of SK channel activation by CyPPA in spinocerebellar ataxia type 2 point to an emerging new therapeutic strategy for neurodegenerative diseases (43)(44)(45).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This is further supported by the fact that in the present model system using immortalized HT-22 neurons cell membrane NMDA receptors are not expressed (41,42), and SK2 channel activation is neuroprotective even in the absence of extracellular Ca 2ϩ . Recent findings on the role of SK channel activation by CyPPA in spinocerebellar ataxia type 2 point to an emerging new therapeutic strategy for neurodegenerative diseases (43)(44)(45).…”
Section: Discussionsupporting
confidence: 64%
“…Our data now show functional expression of SK2 channels at the inner mitochondrial membrane of neuronal cells, providing protective roles under conditions of cellular stress. In particular, we found that inhibition of Ca 2ϩ influx through the plasma membrane only provided partial protection in models of glutamate-induced oxytosis and tBid toxicity (41,42,51) (Figs. 4, 5, and 6).…”
Section: Discussionmentioning
confidence: 93%
“…Since glutathione (GSH) is important antioxidant in CNS and GSH reductase (GR) is a critical enzyme for the production of GSH. High concentration of glutamate leads to deprivation of GSH by inhibiting of cysteine uptake into cells (Albrecht et al ., 2010). Depletion of GSH or antioxidant enzyme, such as GR causes neuronal cell death (Kane et al ., 1993).…”
Section: Resultsmentioning
confidence: 99%
“…These cells originate from the mouse CA1 region and are a suitable model for glutamate-induced toxicity rather than excitotoxicity, as they lack ionotropic GluRs; instead, glutamate blocks the cystine/glutamate antiporter system xc − . 26 Figure 5e). On the other hand, the increase in intracellular ROS correlated to the enhanced dysfunction of mitochondria in HuR lo neurons; this was demonstrated by significant drop in 3,3′-dihexyloxacarbocyanine iodide (DiOC6(3)) marking their membrane potential; and an enhancement in the incorporation of MitoSox marking the augmented release of superoxide from damaged organelles (Figure 3d).…”
Section: Elavl1mentioning
confidence: 97%